Hall's voyage to Repulse Bay - Hall, Charles Francis, 1821-1871 (United States Naval Observatory, 1879)
Shows outward track in 1864 and homeward track in 1869. Relief shown by hachures. Includes inset map of Wager Bay area from "April 27th to June 5th 1865. Differs from that found in: Narrative of the second Arctic expedition made by Charles F. Hall, page 55 . -- this version's title differs and lacks text in bottom margin. This expedition, like his expedition of 1860-1862, was supported by private subscriptions, and both were undertaken to search for the records of the Franklin expedition and to promote and benefit the cause of geography, navigation, natural history and science.